Scalable Manufacturing Processes for Solid Lipid Nanoparticles - Anderluzzi, Giulia; Lou, Gustavo; Su, Yang; Perrie, Yvonne (Pharmaceutical Nanotechnology, 2019)
Background: Solid lipid nanoparticles offer a range of advantages as delivery systems but they are limited by effective manufacturing processes. Objective: In this study, we outline a high-throughput and scalable manufacturing process for solid lipid nanoparticles. Methods: The solid lipid nanoparticles were formulated from a combination of tristearin and 1,2-Distearoyl-phosphatidylethanolamine-methyl-polyethyleneglycol conjugate-2000 and manufactured using the M-110P Microfluidizer processor (Microfluidics Inc, Westwood, Massachusetts, US). Results: The manufacturing process was optimized in terms of the number of process cycles (1 to 5) and operating pressure (20,000 to 30,000 psi). The solid lipid nanoparticles were purified using tangential flow filtration and they were characterized in terms of their size, PDI, Z-potential and protein loading. At-line particle size monitoring was also incorporated within the process. Our results demonstrate that solid lipid nanoparticles can be effectively manufactured using this process at pressures of 20,000 psi with as little as 2 process passes, with purification and removal of non-entrapped protein achieved after 12 diafiltration cycles. Furthermore, the size could be effectively monitored at-line to allow rapid process control monitoring and product validation. Conclusion: Using this method, protein-loaded solid lipid nanoparticles containing a low (1%) and high (16%) Pegylation were manufactured, purified and monitored for particle size using an at-line system demonstrating a scalable process for the manufacture of these nanoparticles.
Keywords: High-throughput manufacturing